The second round of opening-up China's choice at the crossroads of globalization - He Dongni; Xia Feng; Fang Shuanxi; Kuang Xianming (Contemporary China's academic classics, 2017)
This book consists of an introduction and five chapters: based on the analysis of the new challenges of economic globalization, Introduction puts forward some relevant judgments and suggestions on China's economic transformation and structural reform. Chapter 1 and Chapter 2 try to put forward China's choice to 'the Second Round of Opening-up' based on analyzing the objective trend of economic globalization and the new crossroads of globalization; Chapter 3-5 respectively put forward the 'three major strategies' of 'the Secondary Round of the Opening-up', namely, the big strategy of free trade, the big strategy of 'the Belt and the Road' and the big strategy of service trade. 'Three major tasks' of deepening the economic transformation and the structural reform should be completed in 'the Secondary Round of the Opening-up', namely, the structural reform aimed at economic transformation, the major action of opening the service market and the government's role in the regulatory and supervision reform.